Patient and caregiver expectations of emergency department care: A scoping literature review. (May 2017) - Curran, Janet; Cassidy, Christine; Chiasson, Darrell; MacPhee, Shannon; Bishop, Andrea
Highlights: Literature related to patient and caregiver ED expectations is discussed. Paucity of research literature related to patient/caregiver expectations. Majority of studies do not communicate expectations to nurses or other health care providers. Experimental research needed to evaluate strategies for obtaining ED expectations. Abstract: Background: Communication between health care providers (HCPs) and patients and/or their caregivers in the chaotic emergency department (ED) context can be challenging and potentially impact health outcomes and patient satisfaction. Studies examining strategies to improve communication of patient and caregivers expectations of care in an ED are widely dispersed. Methods: We conducted a scoping review of the published and grey literature to examine the extent, range and nature of existing research evidence regarding strategies to enhance communication of patient and caregiver expectations of care in an ED. Results: Of the 599 articles retrieved, 24 met the inclusion criteria. Most of the studies identified included patients (n = 9) or caregivers (n = 8) as the population of interest, while the remainder examined the expectations of a mix of patients, parents/caregivers, and/or HCPs (n = 7). The majority (n = 21) of the studies did not communicate patient/caregiver expectations to HCPs. Conclusion: This scoping review highlights the paucity of available research literature evaluating strategies to communicate patient and caregiver ED expectations. Our findings identify the need for experimental designs in future studies to evaluate implementation strategies for ED expectation tools with a particular emphasis on measuring the impact of sharing patient expectations with HCPs.